Stability Analysis for Buoyancy UTeM’s Amphibious Hybrid Vehicle (AHV) - Hassan, Muhammad Zahir; Abdul Kudus, Syahibudil Ikhwan; Halid, Mohd Shazni; Abdul Manaf, Muhammad Zaidan (TECHNICALJOURNALS-PB Publishing Corporation, 2013)

(untitled)
The buoyancy of the amphibious hybrid vehicle is depending on the parameter of the bottom hull body to keep it afloat every time. Based on the Archimedes principle, the weight of the object float is equal to the volume of water displace. When stimulates on the water surface, there will always resistant that affect the stability of the vehicle. Besides, the stability level of the AHV is very important to ensure the vehicle is on the stable condition and has the ability to face the rollover and pitch effect. Therefore, bottom hull body parameter of the vehicle is not just make it floating, but plays the important role to keep it in the stable state during face the rolling and pitching effect.